Prevalence of central sensitization and neuropathic pain in patients with psoriatic arthritis: A cross-sectional study - Gülay Alp,; İdil Kurut Aysin,; Haluk Cinakli,; Dilek Solmaz,; Servet Akar, (Archives of Rheumatology, 2025)
Objectives: This study aims to evaluate the frequency of central sensitization (CS) and neuropathic pain (NP) in psoriatic arthritis (PsA) and their association with disease activity and functional disability. Patients and methods: Between April 2022 and August 2022, data of a total of 114 consecutive patients (78 males, 36 females; mean age: 49±11.5 years; range, 22 to 76 years) who were diagnosed with PsA according to the classification criteria for PsA criteria were prospectively analyzed. CS was assessed using the Central Sensitization Inventory (CSI), with scores ≥40 indicating its presence. Neuropathic pain was evaluated using the Douleur Neuropathique en 4 Questions (DN4), with scores ≥4 indicating its presence. Results: The median disease duration was 4 (interquartile range: 9) years. Among 114 patients, CS was present in 43% and NP in 23.5%. Fibromyalgia syndrome (FMS) was diagnosed in 25.5%. Patients with CS or NP had higher Visual Analog Scale pain scores, patient and physician global assessments, tender joint counts, disease activity scores in PsA, and Health Assessment Questionnaire Disability Index (HAQ-DI). Central sensitization was also associated with enthesitis, nail involvement, and depression, while NP was linked to higher body mass index (BMI). Anxiety, depression, and HAQ-DI were independent risk factors for CS, while BMI and FMS were correlated with NP. Conclusion: Our study results suggest that CS and NP are prevalent in PsA and are associated with worse disease outcomes. Recognizing and addressing these conditions may enhance the management of patients with refractory symptoms and unmet treatment goals.